Analysis of Gene Expression Rates in Fetal Liver Cryopreserved Cells During Reculturing - Borisov, Petr A.; Dimitrov, Aleksey Yu.; Goltsev, Anatoliy N. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2015)
N/A